A influência do diagnóstico pré-natal na interação da díade mãe-bebê: um estudo longitudinal do pré-natal ao primeiro ano de vida - Vera Cristina Alexandre de Souza (2019)
Introduction: The present study considers the influence of the events of the prenatal period on maternal representations and their consequences on the interaction of the mother-baby dyad. Objectives: The study aims to look at the interactions between the mother and her baby. Rationale: The mother-baby interaction may have an effect on the child’s development and such an effect is measured by observation. Highlighting and classifying quantitatively and/or qualitatively communicative abilities is extremely relevant to understanding the child’s development. Methodology: This is a quantitative, qualitative, descriptive and longitudinal observational study of the development of the mother-baby dyad interaction from the gestational phase to the first year of the baby’s life. The subjects are 50 dyads (mother-baby) from the third gestational trimester. They were divided into two groups: a study group of 25 pregnant women with ultrasound findings of fetal structural anomaly (assisted at CEMEFE – Fetal Medicine Center of the Clinics Hospital of the Federal University of Minas Gerais – UFMG) and a control group of 25 pregnant women with normal ultrasound findings (regularly assisted at the Prenatal Service of Jenny de Andrade Faria Institute of the Clinics Hospital of the Federal University of Minas Gerais – UFMG). The study protocol consists of the analysis of interaction situations, that is, the communicative signs of the dyad at three different moments, with the use of an object / toy, a song sung by the mother and only with the mother's speech. The main tools used in this study were (1) IRMAG, an interview about maternal representations, (2) Covi Anxiety Scale and Raskim Depression Rating Scale, (3) Preaut Protocol, (4) Infant Behavior Questionnaire – Revised, (5) Coding Interactive Behavior (CIB) Questionnaire, a parent-baby interaction classification system that includes level codes and classification scales. Written informed consent was requested from parents or legal guardians of the pregnant women and children. The research project was approved by the Research Ethics Committee of UFMG (CAAE number: 548.79816.0.0000.5149). Results: The study was divided into two stages: Stage 1, prenatal phase and Stage 2, postnatal phase. In Stage 1, the study group and the control group showed substantial differences regarding anxiety severity, depression severity and anxiety and depression severity scales. The severity scores were assigned to the study group. There was no considerable difference between the groups regarding the kind of maternal representations and the mother-baby dyad’s interactive moment (prenatal phase). In Stage 2 there was not any fundamental difference regarding the use of Preaut Protocol or Infant Behavior Questionnaire-Revised. There were significant differences between the groups concerning the analysis of the interaction by “CIB” on the following stages: (1) six months, in regard to the baby’s engagement in different situations (free, object and song), dyad’s reciprocity (free and object) and dyad’s negative states (free and song); (2) nine months, in regard to the baby’s engagement (free) and dyad’s reciprocity (object and song); as to the analysis of grouped situations (free + object + song), the differences between the groups were (a) dyad’s reciprocity, dyad’s negative states and baby withdrawal at six months, (b) mother’s sensitiveness, baby’s engagement and dyad’s reciprocity at nine months and (c) baby’s engagement at twelve months. Conclusion: The effects of prenatal diagnosis became evident in some stages of development, causing significant differences. These differences between the groups revealed that the presence of prenatal diagnosis did not compromise the type of maternal representation and had no negative effect on the quality of the mother-baby interaction during the first year of life.